Kontribusi Kompetensi Guru terhadap Kinerja Guru Pendidikan Jasmani - Andani, Lina Farda; Hanani, Endang Sri; Wahyudi, Agung; Solastri, Solastri; Trinanda, Aditya (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to determine the contribution of teacher competence to physical education performance in the city of Purworejo. This type of research is quantitative with a correlational descriptive method. The sample consisted of 31 teachers consisting of 21 physical education teachers and 10 school principals. Data collection techniques use observation, questionnaires, and documentation with data analysis techniques using normality tests, linearity tests, homogeneity tests, and hypothesis tests. The results show that the contribution of pedagogical competence to the performance of physical education teachers in Purworejo City is 68.1%, the contribution of personality competence is 40.4%, the contribution of professional competence is 57.6%, and the contribution of social competence is 15.2%. In conclusion, of the four teacher competencies, the highest contribution is pedagogical competence to the performance of junior high school physical education teachers in Purworejo City at 68.1% and the lowest is social competence to the performance of junior high school physical education teachers in Purworejo City at 15.2%. Keywords: Physical Education, Teacher Competency, Teacher Performance